Remote physiological systems (RePhyS) laboratory: a didactic learning environment - Barros, C. (2013)
With the appearance of new teaching/learning methods, innovative techniques have been used to motivate and to improve students' skills in the area of engineering. Nowadays, remote laboratories are well accepted and used to support the students' learning in higher education, playing an important role in engineering teaching, since they allow the connection between theory and practice to all students anytime, anywhere because they are available in the Internet. Following this trend, this paper describes the main ideas of a multidisciplinary R&D workgroup in the development of an innovative laboratory in the bioengineering area: RePhyS. RePhyS is a remote laboratory for the study of biomedical and physiological systems in graduate and post graduate levels. The user (student) will be allowed to interact with the system parameters, through an interface, controlling and monitoring the process, in real-time, and receiving the selected results.